Comparison of the antisclerotic effect of hydroalcoholic extracts of Ocimum basilicum and Otostegia persica with quinacrine by inhibition of phospholipase A2 in male Wistar rats - Fatemeh Ghanbarpour Rahdari; Kahin Shahanipour; Ramesh Monajemi; Mohammad Adibnejad (Mashhad University of Medical Sciences, 2022)
Objective: Hypercholesterolemia is now considered a major risk factor for development of atherosclerosis. The phospholipase A2 superfamily of enzymes has causal involvement in atherosclerosis. Atherosclerosis is one of the main causes of mortality in developed countries and in some developing countries such as Iran. The present study was designed to investigate the antihypercholesterolemic and antiatherogenic potentiality of ethanolic extracts of Ocimum basilicum (O. basilicum) and Otostegia persica (O. persica) in high-fat diet-induced hypercholesterolemic rats.Materials and Methods: In this study, 35 male rats were randomly divided into 1 normal diet and 4 high-fat diet groups. After two months of high-fat diet, measurement of cholesterol and LDL showed a significant difference between the groups. The 5 groups were as follows: Healthy rats receiving physiological serum, hypercholesterolemic rats without any treatment, hypercholesterolemic rats receiving quinacrine (30 mg/kg), hypercholesterolemic rats treated with extract of O. persica (300 mg/kg), and hypercholesterolemic rats treated with O. basilicum extract (300 mg/kg). Treatment was carried out for 40 days and finally, blood samples were collected and examined for cholesterol, triglyceride, high density lipoprotein, low density lipoprotein, C-reactive protein, phospholipase A2, and interleukin-6 levels.Results: Treatment of hypercholesterolemic rats with ethanolic extracts of O. persica and O. basilicum did not cause significant changes in cholesterol, triglyceride and LDL or HDL levels. They caused a significant decrease in the levels of inflammatory factors of IL-6, PLA2 and CRP (p <0.05).Conclusion: Ethanolic extracts of O. persica and O. basilicum have antisclerotic effects by reducing the inflammatory factors and PLA2 activity.